Observed Antagonistic Effect of Linezolid on Daptomycin or Vancomycin Activity against Biofilm-Forming Methicillin-Resistant Staphylococcus aureus in an In Vitro Pharmacodynamic Model - Luther, Megan K. (Antimicrob Agents Chemother, 2015)
Pharmacodynamic activity in antibiotic combinations of daptomycin, vancomycin, and linezolid was investigated in a 48-h in vitro pharmacodynamic model. Using human-simulated free drug concentrations, activity against clinical biofilm-forming methicillin-resistant Staphylococcus aureus isolates was evaluated. Linezolid antagonized vancomycin activity at 24 and 48 h. Linezolid antagonized daptomycin at 24 and 48 h depending on dose and strain. Adding daptomycin increased vancomycin activity at 48 h (P < 0.03). These results may be strain dependent and require further clinical investigation.